Guar Meal as a Substitute for Conventional Soyabean Meal: Impact on Blood and Serum Profile of Nagavali Ram Lambs - Shweta, Nanda; Rani, K. Sudha; Kumar, D. Srinivas; Illa, Satish Kumar (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during 2024 from April to June for a period of 90 days, at Livestock Research station, Garividi, Vizianagaram district, Andhra Pradesh, India. The research was focused on guar meal, a non-conventional feed ingredient for substituting soyabean meal in sheep concentrate feed and its effect on haematology and serum profile. A 90-day trial was conducted using 24 Nagavali ram lambs, with an average body weight of 7.4 kg and ages ranging from 3 to 6 months. The lambs were randomly assigned to four dietary treatments. The control diet was formulated with concentrate mixture and super napier green fodder. In the treatment diets, guar meal replaced soybean meal at 50%, 75%, and 100% levels. Blood and serum samples were collected in EDTA and serum vials at the beginning (0th day) and end (90th day) of the trial for analysis of various haematological parameters and serum was separated by centrifugation and subjected to various serological tests to analyse lipid profile, mineral profile, liver and kidney function of the guar meal fed lambs. No significant (p>0.05) differences were noticed in both blood and serum parameters before and after feeding with guar meal among the four dietary groups, and all the values were in normal physiological range indicating that guar meal can effectively replace soybean meal as a protein source in sheep diets.